2021
DOI: 10.1002/rth2.12545
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐methods study to evaluate a patient‐designed tool to reduce harm from cancer‐associated thrombosis: The EMPOWER study

Abstract: Introduction Venous thromboembolism (VTE) is a common and serious complication of systemic anticancer therapies. Delays in presentation increase risk of death or long‐term morbidity. Background A patient charity developed an information video for patients receiving systemic anticancer therapy including what to do if they developed symptoms of VTE. This was introduced into clinical practice in a regional cancer center and its impact compared with a district general hospital where the video was not used. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The validity of a mixed‐methods, patient‐centered strategy for CAT education has been suggested by a Welsh experience in which an information video was developed and delivered to patients receiving systemic anti‐cancer therapy leading to shorter mean time to presentation with VTE symptoms (from 8.9 to 2.9 days), possibly reflecting greater CAT awareness resulting in earlier recognition and clinical consultation. 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of a mixed‐methods, patient‐centered strategy for CAT education has been suggested by a Welsh experience in which an information video was developed and delivered to patients receiving systemic anti‐cancer therapy leading to shorter mean time to presentation with VTE symptoms (from 8.9 to 2.9 days), possibly reflecting greater CAT awareness resulting in earlier recognition and clinical consultation. 12 …”
Section: Resultsmentioning
confidence: 99%
“…These shall encompass multiple structured interventions that actively and cooperatively engage patients and their caregiver as well as cancer patients' associations, cancer care professionals, scientific societies, industry, and policy makers. The validity of a mixed‐methods, patient‐centered strategy for CAT education has been suggested by a Welsh experience in which an information video was developed and delivered to patients receiving systemic anti‐cancer therapy leading to shorter mean time to presentation with VTE symptoms (from 8.9 to 2.9 days), possibly reflecting greater CAT awareness resulting in earlier recognition and clinical consultation 12 …”
Section: Resultsmentioning
confidence: 99%
“…This may have been because the seriousness of thrombosis was not realised, perhaps as a consequence of a more physician-led clinical decision making style [ 14 ]. Despite calls for routine education for patients regarding the risk of thrombosis [ 11 ] and a recent trial of a patient-education video reducing presentation delays from a mean 8.9 to 2.9 days supporting the use of education materials in this way, this still does not happen in practice [ 31 ]. Further, it brings into question oncologists’ training, and suggests a need for a lower threshold to consider thrombosis as an explanation for new or worsening signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The EMPOWER study in patients receiving systemic anticancer therapy demonstrated the use of a patient information video regarding the risk of VTE significantly reducing the time to presentation with symptoms from 8.9 to 2.9 days (95% CI, 4.5-7.4; hazard ratio [HR], 0.33). [ 39 ] Given the majority of HA-VTE occur post–hospital discharge, strategies to enhance the delivery of patient information at discharge warrant further evaluation. Efforts should be made to ensure that all patients receive information in some form at the time of hospital discharge.…”
Section: Interventions To Improve the Provision Of Thromboprophylaxismentioning
confidence: 99%
“…[ 44 ] This requires investment in staff (or technology) and likely contributes to observations of higher HA-VTE rates in hospitals with higher standards of VTE prevention, due to surveillance bias associated with increased awareness and investigation for VTE. [ 39 , 49 ] Falling rates of autopsy likely contribute to the underreporting of deaths due to HA-VTE, as many such events are not clinically suspected. [ 7 ] However, within single systems, there is likely to be little variation over time, and outcome monitoring is useful both to demonstrate the impact of interventions, and also to identify areas in need of further attention.…”
Section: Challengesmentioning
confidence: 99%